PENDAMPINGAN MASYARAKAT DALAM MEMAKSIMALKAN SISTEM PEMASARAN KERIPIK PISANG LINGKUP PASAR ONLINE DAN OFFLINE DI DESA DILEM KECAMATAN GONDANGKABUPATEN MOJOKERTO - Mohamad Ghozi; Amru Almu’tasim (Universitas Nahdlatul Ulama Sidoarjo, 2020)
Dilem Village, Gondang Subdistrict, Mojokerto Regency is a fertile village at the foot of Mount Arjuna, the majority of the population is agricultural laborers and Perhutani land managers. The most abundant crops are cassava, sweet potato and banana. The plantation products are produced into ready-to-eat food in the form of cassava chips, sweet potato chips, banana chips. However, residents cannot maximize the marketing of their products. In fact, middlemen and traders get huge profits. The middlemen and traders got multiple profits due to their proficiency in packaging and marketing.Assistance to rural communities or farm workers regarding the banana chip marketing system in the online and offline market scope is an answer to the concern of the Dilem village community about increasing economic value. Over the years, the quantity of banana chips production has increased, but the output or enlargement is still traditional (offline) and the packaging is less attractive so it is far from professional, therefore this gap is what drives us the PPM Team Lecturers of the IAI Uluwiyah Islamic Religious Education Study Program to resolving the problems that are being felt by the Dilem village community.This assistance is community empowerment, the lecturer team only functions as a facilitator, while the initial steps taken by the Lecturer PPM Team are to help with attractive packaging and then continue with promotion through online and offline marketing systems which are a form of marketing strategy that is right for this problem. The impact or implication of this assistance is an effort to improve the development of home industries run by residents in order to develop better quality and quantity of production.